A new agglutinated foraminiferal species (Arenoturrispirillina waskowskae sp. nov.) from the Danian of Contessa, Italy - Hikmahtiar, Syouma; Kaminski, Michael A. (Geology, Geophysics and Environment, 2022)
This paper describes a new Paleogene deep-water agglutinated foraminifera from the Contessa Highway Section, Umbria-Marche Basin, Italy. The new species Arenoturrispirillina waskowskae is characterised by its predominently high trochospiral coiling, which distinguishes it from the genus Glomospira. The new species is also found in the Polish Carpathians.